Silbato: Linking Female Officers to Community Traffic Rules and Regulations - Sierto, Maricel E.; Navarro, Ricky J. (Future Science / FSH-PH Publications, 2024)
The study’s primary goal is to identify the struggles faced by female traffic officers with the implementation of community rules and regulations and how they handle problems on the road. In particular, this study wanted answers to the following questions: (1) What are the challenges faced by female officers in implementing community traffic rules and regulations? (2) What are the advantages of the female gender as traffic officers? (3) What are the disadvantages of complaints as traffic officers? and (4) How female enforcers handle complaint/s (if any) by the violators of traffic law? The study will use qualitative research design in which researchers will gather data through interviews. The results show that (1) Every day, traffic enforcers face various difficulties in the enactment of their duties, but they find means to overcome them. Some of these incidents involve reckless drivers, passengers, and pedestrians who fail to adhere to traffic regulations, as well as dealing with traffic and violators in the rain; (2) Extreme tolerance can be applied when approaching drivers as a traffic enforcer. In order to resolve the matter, it is imperative that the superiors approach them with calmness, patience, and respect; (3) Female enforcers experienced harassment, opposition and intimidation by anyone who observes law and order, with some offenders claiming they have done nothing wrong; and (4) In order to minimize misunderstandings between traffic violators, it is important that traffic officers treat them with great respect, regardless of their appearance.